THE PREVALENCE AND CORRELATED FACTORS OF SELF-REPORTED SUICIDAL BEHAVIOR AMONG INDIVIDUALS WITH DISABILITIES - Muhammad Haris Khan Khattak; Rabia Rasheed; Syeda Maryam Gillani; Muhammad Farhan; Anam Qasim; Syeda Manal Fatima (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Disability in Pakistan marginalizes a large percentage of the population. Both global pre- and post-pandemic research shows that people with disabilities are more likely to acquire mental health disorders, which raises their risk of self-harm and suicide. Understanding and resolving disability-related mental health issues is crucial to their community integration and Lahore’s socioeconomic progress. However, Lahore lacks comprehensive data on disability-related suicide prevalence and causes. Thus, this study seeks to understand the extent and causes of suicide behavior in this population to inform targeted interventions and support systems. Lahore’s three divisions’ disabled residents were surveyed cross-sectional in September and October 2023 using probability proportional to size sampling. Socio-demographic, lifestyle, and health data were collected using a semi-structured questionnaire and the SBQ-R. Chi-square test was applied to examine determinants’ effects on mental health. At an SBQ-R score cut-off of 7, 10.45% of individuals reported suicidal behavior, including ideation, attempts, or completion. At least 40% of respondents had suicidal thoughts at some point, and 9.01% did so in the past year. 8.87% of subjects told family members they were suicidal, and 5.94% predicted suicide. Female gender, various disabilities, and family and friend isolation were substantially connected with suicidal behavior. This study emphasizes the necessity of addressing mental health concerns and improving service accessibility to reduce disability challenges. These findings can help policymakers develop large-scale research and implement suicide prevention and management approaches for susceptible groups.